Understanding and measurement: perspectives on the evolution of knowledge-based development. (1st January 2012) - Carrillo, Francisco Javier; Batra, Surinder
This paper traces the symbiotic relationship between the theoretical frameworks of knowledge-based development and the complexity of its measurement. The measurement challenges of KBD essentially flow from the inherent difficulties of measuring non-monetary value. As the KBD under focus progresses towards higher levels of scope and complexity, the measurement challenges tend to increase. Currently, a wide range of KBD dimensions get measured through deliberately designed metrics and composite indicators. The paper highlights certain well-known international initiatives for measuring KBD. It also outlines the ongoing collaborative efforts in the research on KBD metrics and the challenges of developing KBD metrics in the Indian context. Thus, a wide portrayal of the state-of-the-art on the theoretical and methodological foundations of KBD, current research on KBD metrics and some emerging lines of development have been provided.